Pengembangan Video Tutorial Pembuatan Desain Blouse dan Rok Sesuai Kolase pada Mata Pelajaran Dasar Keahlian Busana Kelas X SMKN 8 Surabaya - Engki Edi Saputra; Inty Nahari; Imami Arum Tri Rahayu; Deny Arifiana (Journal on Education, 2024)
This research aims to determine the level of appropriateness and to determine student learning outcomes regarding the video tutorial media for Making Blouse and Skirt Designs According to Collage in the Basic Subject of Clothing Skills Class X SMK Negeri 8 Surabaya. This research using the ADDIE model (Analysis, Design, Development, Implementation and Evaluation). The data collection method uses a media suitability assessment questionnaire by Material Experts, Media Experts and Subject Teachers also a cognitive and psychomotor test sheets for students. The data analysis technique uses descriptive analysis techniques. The research results shown, (1) The level of appropriateness of the media by Material Experts with an average score of 3.58 which is declared Very Good. The level of media suitability by Media Experts with an average score of 3.31 is declared Very Good. The level of suitability of the media by Subject Teachers with an average score of 3.67 from the learning aspect and 3.56 from the media & visual aspect which was declared Very Good. (2) The students learning results were stated as 100% complete KKTP.